1977
DOI: 10.5962/bhl.title.123974
|View full text |Cite
|
Sign up to set email alerts
|

A guide to the management of recent mammal collections

Abstract: From the date of issuance of the permit, the permittee shall maintain complete and accurate records of any taking, possession, transportation, sale, purchase, barter, exportation, or importation of wildlife pursuant to such permit. Such records shall be kept current and shall include names and addresses of persons with whom any wildlife has been purchased, sold, bartered, or otherwise transferred, and the date of such transaction, and such other information as may be required or appropriate. Such records, unle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
1
3

Year Published

1981
1981
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 51 publications
3
41
1
3
Order By: Relevance
“…For details, see Nogueira & Pol (1998 Oliveira et al (2003), is based on the specimens reported here. They present a truly white ventral pelage coloration, not seen in any other pale-bellied Micronycteris (Simmons 1996), and their calcar is similar in size to their foot, which is another useful diagnostic feature of this species (Williams & Genoways 2008). We noticed, however, that the specimens from Jaíba are somewhat larger, in cranial length, than the specimens in the type series (e.g.…”
Section: Family Erethizonthidaecontrasting
confidence: 39%
“…For details, see Nogueira & Pol (1998 Oliveira et al (2003), is based on the specimens reported here. They present a truly white ventral pelage coloration, not seen in any other pale-bellied Micronycteris (Simmons 1996), and their calcar is similar in size to their foot, which is another useful diagnostic feature of this species (Williams & Genoways 2008). We noticed, however, that the specimens from Jaíba are somewhat larger, in cranial length, than the specimens in the type series (e.g.…”
Section: Family Erethizonthidaecontrasting
confidence: 39%
“…7 Micronycteris sanborni was previously thought to occur in Bolivia, but Siles et al (2013) revised the Bolivian material attributed to this species and concluded that it corresponds to a distinct new species, M. yatesi Siles & Brooks, 2013. 8 Williams and Genoways (2008) placed authorship and date of Micronycteris schmidtorum in parentheses, but this species was originally described in its current genus. 9 Listed for the first time for Brazil in the species distribution map proposed by Koopman (1982), but without record of locality or voucher material.…”
Section: Eger (2008) Usnm 393767mentioning
confidence: 99%
“…6 Initially proposed as a subspecies of Micronycteris megalotis (Pirlot, 1967), M. homezorum was re-described as a separated species by Simmons and Voss (1998), and subsequently suggested to be a junior synonym of M. minuta by Ochoa and Sanchez (2005). Porter et al (2007) followed Ochoa and Sanchez (2005), but Williams and Genoways (2008) maintained M. homezorum as a valid species. We also recognized M. homezorum as re-diagnosed by Simmons and Voss (1998), but follow Solari (2008) for the spelling of the specific epithet (M. homezorum instead of M. homezi).…”
Section: Eger (2008) Usnm 393767mentioning
confidence: 99%
See 2 more Smart Citations